Toxic Epidermal Necrolysis A Diagnostic Dilemma in Puerperium: A Case Report - Vidya Mahto (Journal of Nepal Medical Association, 2019)
Toxic epidermal necrolysis is a potentially life threatening dermatologic disorder characterized by widespread erythema, necrosis and bullas, detachment of epidermis and mucous membrane resulting in exfoliation, possible sepsis and even death. This is the first case report in Nepal of toxic epidermal necrolysis in puerperium. We present a case of a 28-years-old, P1L1 on fourth postoperative day following emergency lower segment caesarean section for cephalopelvic disproportion in latent phase of labour with uneventful antenatal period. She developed fever followed by rashes all over the body with hypotension, tachypnea and shortness of breath. Initially, she was diagnosed as a case of septic shock and transferred to intensive care unit from postnatal ward. She was managed with broad spectrum antibiotics and inotropes. Later on, it was found to be the case of Toxic epidermal necrolysis and managed with vancomycin and corticosteroids under the supervision of gynecology, dermatology and medicine team.